2011
DOI: 10.5530/pj.2011.20.7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activities of Ficus benghalensis bark against carbohydrate hydrolyzing enzymes - An in vitro study

Abstract: the present study evaluated the effect of Ficus benghalensis linn. (Moraceae) stem bark on porcine pancreatic α-amylase, rat intestinal α-glucosidase and sucrase. Further, the effect of heat treatment was also studied. Both untreated and heattreated samples inhibited α-amylase to a significant extent. Further, the aqueous extracts prepared form untreated and heat treated samples exhibited significant inhibition (p ≤ 0.05) of α-glucosidase and sucrase in a dose dependent manner. Heat treatment of the sample inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Isolated 6‐O‐acyl‐β‐D‐glucosyl‐β‐sitosterols (6‐AGS) from F. carica latex showed anticancer activities against many cancer cells such as Burkitt B‐cell lymphoma (DG‐75 cells) and T‐cell leukemia (Jurkat cells) (Rubnov et al., 2001). The fruit of F. carica and bark of F. benghalensis have been reported for their potent antidiabetic properties by inhibiting α‐glucosidase enzyme in vitro (Ahmed et al., 2011; Wojdyło et al., 2016), leading to reduced glucose absorption in the intestinal tract. Ficus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated 6‐O‐acyl‐β‐D‐glucosyl‐β‐sitosterols (6‐AGS) from F. carica latex showed anticancer activities against many cancer cells such as Burkitt B‐cell lymphoma (DG‐75 cells) and T‐cell leukemia (Jurkat cells) (Rubnov et al., 2001). The fruit of F. carica and bark of F. benghalensis have been reported for their potent antidiabetic properties by inhibiting α‐glucosidase enzyme in vitro (Ahmed et al., 2011; Wojdyło et al., 2016), leading to reduced glucose absorption in the intestinal tract. Ficus spp.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore believe that the glucose lowering potential demonstrated in vivo by the extract of F. sycomorus may be due to the inhibition of α-glucosidase activity (sucrase). Some authors have shown that the extracts of other Ficus species such as F. racemose [60], F. benghalensis [61] and F. deltoidea [62] inhibit the activity of sucrase with an EC50 of 367 ± 15.2 μg/ml and 239 ± 14.3 μg/ml respectively for cold and hot water extract of F. racemosa , and 193 ± 21.6 μg/ml and 141 ± 22.1 μg/ml respectively for cold and hot water extract of F. benghalensis . This was in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The liberation of glucose was greatly inhibited by FRB in amylolysis kinetics. Furthermore, it increased the rate of glucose transport across the yeast cell membrane and in isolated rat hemi-diaphragm and inhibited α-amylase, α-glucosidase, β-glucosidase and sucrase in a dose dependent manner indicating a strong hypoglycemic effect in vitro and ex vivo [13][14][15]. Similar observations were noted with reference to Morus indica, wherein the sample effectively inhibited the digestion of starch and also inhibited the movement of liberated glucose across the dialysis membrane which could be attributed to the inhibition of carbohydrate hydrolyzing enzymes.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%